Two new quinic acid derivatives from the leaves of Schisandra chinensis. Issue 7 (3rd July 2022) - Bai, Jin-Ting; Liu, Yan; Sun, Yan-Ping; Liu, Guo-Zhen; Li, Xiao-Mao; Wang, Si-Yi; Algradi, Adnan Mohammed; Pan, Juan; Guan, Wei; Yang, Bing-You; Kuang, Hai-Xue
Abstract: Two new (1-2 ) and three known quinic acid derivatives (3-5 ) were isolated from the leaves of Schisandra chinensis (Turcz) Baill. The structures of the compounds were determined by spectroscopic methods, especially the NMR techniques, and also by comparison with reported data in the literature. The cytotoxicity activities of these compounds were evaluated on human tumor cell lines LN229 and three of them showed a certain activity. Abstract : UF0001